Fine Particulate Matter Induces Childhood Asthma Attacks via Extracellular Vesicle‐Packaged Let‐7i‐5p‐Mediated Modulation of the MAPK Signaling Pathway. Issue 3 (23rd November 2021) - Zheng, Rui; Du, Mulong; Tian, Man; Zhu, Zhaozhong; Wei, Chengcheng; Chu, Haiyan; Gan, Cong; Liang, Jiayuan; Xue, Renjie; Gao, Fang; Mao, Zhenguang; Wang, Meilin; et al.
Abstract: Fine particulate matter less than 2.5 µm in diameter (PM2.5 ) is a major risk factor for acute asthma attacks in children. However, the biological mechanism underlying this association remains unclear. In the present study, PM2.5 ‐treated HBE cells‐secreted extracellular vesicles (PM2.5 ‐EVs) caused cytotoxicity in "horizontal" HBE cells and increased the contractility of "longitudinal" sensitive human bronchial smooth muscle cells (HBSMCs). RNA sequencing showed that let‐7i‐5p is significantly overexpressed in PM2.5 ‐EVs and asthmatic plasma; additionally, its level is correlated with PM2.5 exposure in children with asthma. The combination of EV‐packaged let‐7i‐5p and the traditional clinical biomarker IgE exhibits the best diagnostic performance (area under the curve [AUC] = 0.855, 95% CI = 0.786–0.923). Mechanistically, let‐7i‐5p is packaged into PM2.5 ‐EVs by interacting with ELAVL1 and internalized by both "horizontal" recipient HBE cells and "longitudinal" recipient‐sensitive HBSMCs, with subsequent activation of the MAPK signaling pathway via suppression of its target DUSP1 . Furthermore, an injection of EV‐packaged let‐7i‐5p into PM2.5 ‐treated juvenile mice aggravated asthma symptoms. This comprehensive study deciphered the remodeling of the extracellular environment mediated by the secretion of let‐7i‐5p‐enriched EVs during PM2.5 ‐induced asthma attacks and identified plasma EV‐packaged let‐7i‐5p as a novel predictor of childhood asthma. Abstract : PM2.5 is considered an important type of allergen in childhood asthma. Let‐7i‐5p is packaged into EVs though an interaction with ELAVL1 and then internalized by recipient cells (HBE and sensitive HBSMCs). EV‐packaged let‐7i‐5p activate the MAPK signaling pathway by targeting DUSP1, resulting in cytotoxicity in "horizontal" recipient HBE cells and enhance contractility of "longitudinal" recipient‐sensitive HBSMCs.